Pengaruh Kegiatan Pembangkit Listrik Tenaga Gas dan Uap PT X Terhadap Emisi Gas SO2 dan NOx - Mukharomah, Nur Laili Alfiatin; Ningrum, Dwi Mulyati; Claudya, Agnes Lidya (Envirous, 2025)
Climate change is a global phenomenon that triggers social and ecological crises. Indonesia has committed to the Sustainable Development Goals (SDGs) to reduce greenhouse gas (GHG) emissions as stated in the Nationally Determined Contribution (NDC). The NDC targets lowering emissions by 41% by 2030 with independent efforts and international assistance. This study aims to analyze SO2 and NOx emissions from the Gas and Steam Power Plant (PLTGU) at X Company, with reference to the applicable air quality standards, namely the Regulation of the Director General of Pollution Control and Environmental Damage Number P.17/PPKL/PPU/KUM.1/10/2022. The methods used in the analysis process are USEPA Method 6C: 2017 in determining Sulfur Dioxide (SO2) gas and USEPA Method 7E: 2020 in determining Nitrogen Oxide (NOx) gas. Field measurements were conducted at several sampling points in HRSG Blocks II.1, II.2, and II.3. The analysis results show that the SO2 and NOx emission concentrations are still below the maximum permissible limits with the highest SO2 and NOx emission concentrations of 291 Mg/Nm³ and 6 Mg/Nm³, respectively